If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -40 + 3y + 4 = 2(3y + -3) + -9 Reorder the terms: -40 + 4 + 3y = 2(3y + -3) + -9 Combine like terms: -40 + 4 = -36 -36 + 3y = 2(3y + -3) + -9 Reorder the terms: -36 + 3y = 2(-3 + 3y) + -9 -36 + 3y = (-3 * 2 + 3y * 2) + -9 -36 + 3y = (-6 + 6y) + -9 Reorder the terms: -36 + 3y = -6 + -9 + 6y Combine like terms: -6 + -9 = -15 -36 + 3y = -15 + 6y Solving -36 + 3y = -15 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -36 + 3y + -6y = -15 + 6y + -6y Combine like terms: 3y + -6y = -3y -36 + -3y = -15 + 6y + -6y Combine like terms: 6y + -6y = 0 -36 + -3y = -15 + 0 -36 + -3y = -15 Add '36' to each side of the equation. -36 + 36 + -3y = -15 + 36 Combine like terms: -36 + 36 = 0 0 + -3y = -15 + 36 -3y = -15 + 36 Combine like terms: -15 + 36 = 21 -3y = 21 Divide each side by '-3'. y = -7 Simplifying y = -7
| ln(x+1)+ln(x+1)=4 | | 0.4b=390 | | 3(r-3)-1=2r+9 | | 7x+x=33 | | g(3)=3.2(3)+2.8 | | 49=7k | | 7(c-3)+9=6-c-18 | | 7x+149=5x+125 | | 49=ik | | 9n+n=2n-8 | | 93=31h | | 4b+5b=81 | | 17y=102 | | 8f+6=22 | | 9g=45 | | x-(-4)=x+9 | | 9x+210=7x+176 | | 8b=56 | | 19v-7v=108 | | -2k+3k-6+2k= | | 11x-30=360 | | 6n+5=6n+18 | | 7y+12-3y+8-4y= | | 10x-79=2x+49 | | 12x^2+15x+18= | | .2x^2+1.2=3.4 | | 6b=60 | | 2a+10=7/3 | | 6.1(3x+7)=134.2 | | q^2-5q-24= | | 2b=36 | | 8s(8+6s)=20 |